USAGE OF PYROLYSIS HEAVY RESIN FOR THE PETROLEUM BITUMEN PRODUCTION - Fryder, Iryna; Grynyshyn, Oleg; Khlibyshyn, Yuriy (Proceedings of National Aviation University (archive), 2014)
The investigation results of tar and pyrolysis heavy resin joint oxidation, as well as the results of commercial bitumen modification by pyrolysis heavy resin are presented. The possibility of the latter compound usage in the processes of petroleum bitumen production is shown.